Perovskite Solar Cells: Mixed Valence Perovskite Cs2Au2I6: A Potential Material for Thin‐Film Pb‐Free Photovoltaic Cells with Ultrahigh Efficiency (Adv. Mater. 12/2018). Issue 12 (25th March 2018) - Debbichi, Lamjed; Lee, Songju; Cho, Hyunyoung; Rappe, Andrew M.; Hong, Ki‐Ha; Jang, Min Seok; Kim, Hyungjun
Abstract : In article number1707001, Min‐Seok Jang, Hyungjun Kim, and co‐workers propose gold‐based halide perovskites as a lead‐free and stable material for very‐thin‐film perovskite solar cells (PSCs). Using a multiscale simulation, this already‐existing material is found to have ideal optical properties for PSCs. This work is expected to inspire work toward the realization of this new concept in PSCs based on mixed‐valence perovskites.